2008
DOI: 10.1016/j.ajog.2008.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic effects of epithelial ion channels on the mouse uterus: differences between raloxifene analog (LY117018) and estradiol treatments

Abstract: Estradiol and LY117018 differentially regulate the expression of CFTR and ENaC in ovariectomized mouse uterus. This finding suggests that uterine fluid accumulation can be controlled mainly by targeting the ENaC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Previous studies demonstrate that ENaC is primarily localized to the apical membrane of both luminal and glandular epithelia, while CFTR is predominantly expressed in the stromal cells (Chan et al, 2002; Ruan et al, 2012; Yang et al, 2004). Estrogen induces CFTR expression, but represses ENaC, resulting in fluid accumulation in the uterine lumen, whereas progesterone acts oppositely in regulating these two genes for fluid reabsorption in the uterus (Nobuzane et al, 2008; Zheng et al, 2004). Abnormal uterine fluid accumulation and implantation failure have also been observed when CFTR expression is aberrantly upregulated by inflammation in mice (He et al, 2010).…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%
“…Previous studies demonstrate that ENaC is primarily localized to the apical membrane of both luminal and glandular epithelia, while CFTR is predominantly expressed in the stromal cells (Chan et al, 2002; Ruan et al, 2012; Yang et al, 2004). Estrogen induces CFTR expression, but represses ENaC, resulting in fluid accumulation in the uterine lumen, whereas progesterone acts oppositely in regulating these two genes for fluid reabsorption in the uterus (Nobuzane et al, 2008; Zheng et al, 2004). Abnormal uterine fluid accumulation and implantation failure have also been observed when CFTR expression is aberrantly upregulated by inflammation in mice (He et al, 2010).…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%
“…Aberrant upregulation of CFTR or inhibition of uterine ENaC leads to abnormal uterine fluid accumulation and implantation failure. Progesterone has been shown to repress the expression of CFTR while stimulating uterine ENaC induction, which is condu- cive to embryo implantation (Nobuzane et al, 2008, Zheng et al, 2004. Moreover, it has been shown that serum and glucocorticoid inducible kinase-1 (SGK1), a key regulator of sodium transport in mammalian epithelia (Fejes-Toth et al, 2008), can enhance ENaC expression via inhibiting the ubiquitin ligase, neural precursor cell expressed developmentally down-regulated protein (NEDD) 4-2 (Lang et al, 2006).…”
Section: Luminal Closurementioning
confidence: 99%
“…For example, interplay between the cystic fibrosis transmembrane conductance regulator (CFTR) and epithelial sodium channel (ENaC), as well as potassium (K 1 ) channels, are vital in regulating uterine electrolyte and fluid transport. This is very important in terms of reducing the volume of uterine luminal fluid, in order to lock the embryo in place prior to implantation (Nobuzane et al, 2008). ENaC also senses mechanical and chemical signals from the embryo and transduces downstream cellular responses to promote stromal decidualization (Enuka et al, 2012;Ruan et al, 2014).…”
Section: Ion Channelsmentioning
confidence: 99%